2021
DOI: 10.3389/fimmu.2021.717879
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Placental Vesicles Carry HLA-DR in Pre-Eclampsia: A New Potential Marker of the Syndrome

Abstract: BackgroundPre-eclampsia (PE) is a common disorder of pregnancy that usually presents with hypertension and proteinuria. The clinical presentation arises from soluble factors released into the maternal circulation from the placenta owing to the stress of syncytiotrophoblast, consequence of defective placentation occurring in the first half of pregnancy. Reduced tolerance of the semiallogeneic fetus by the maternal immune system has been proposed as first trigger leading to poor placentation. We previously obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Out of sixteen patients with HLA-DR-positive STEVs in the first trimester, six developed PE (38%), with a prevalence of STEV HLA-DR positivity in PE cases, consistent with previous observations [6,7]. A significant difference was found between the non-PE and PE groups in terms of HLA-DR positivity of STEVs during the first trimester of pregnancy (Figure 4a).…”
Section: Levels Of Hla-dr+ Stevs and Plgf In Pesupporting
confidence: 89%
See 1 more Smart Citation
“…Out of sixteen patients with HLA-DR-positive STEVs in the first trimester, six developed PE (38%), with a prevalence of STEV HLA-DR positivity in PE cases, consistent with previous observations [6,7]. A significant difference was found between the non-PE and PE groups in terms of HLA-DR positivity of STEVs during the first trimester of pregnancy (Figure 4a).…”
Section: Levels Of Hla-dr+ Stevs and Plgf In Pesupporting
confidence: 89%
“…In a previous study, aberrant expression of the HLA-DR antigen was found in approximately 40% of STEVs obtained from PE women by double placenta perfusion and confirmed by immunohistochemistry on placental sections [6] A subsequent study from the same group demonstrated the abnormal expression of HLA-DR in serum STEVs in women with clinically overt PE (64%) during the third trimester of pregnancy. None of the normal pregnant women showed detectable positivity for HLA-DR in circulating STEVs [7].…”
Section: Introductionmentioning
confidence: 88%
“…Investigation of EV populations deriving from a specific cell type, via surface marker phenotyping, was performed in 58/152 studies. We reviewed the quantification data from 54 of these, as the remaining four presented data as fold‐change, % of EVs of specific cellular derivation, flow cytometric plots without numbers, or without absolute counts of particles (Pap et al., 2008; Tersigni et al., 2021; Walenta et al., 2012; Wong et al., 2015). The concentration of cell‐specific EVs in the blood of healthy non‐pregnant, healthy pregnant, or pathological pregnant participants, measured by either flow cytometry (FC) or fNTA, are summarised in Figure 8a.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have demonstrated PLAP+ EVs in maternal blood. PLAP is present both in small EVs of a size consistent with exosomes and microvesicles [83,84,86,89,90], and in larger SNAs [91][92][93][94][95][96].…”
Section: Placental Alkaline Phosphatase (Plap)mentioning
confidence: 99%
“…Surface markers include general EV biomarkers such as CD63, as well as tissue-specific markers such as PLAP. Many studies have shown that placental-derived EVs are altered in diseases such as pre-eclampsia, gestational diabetes mellitus and intrauterine growth restrictions [86,89,90,[92][93][94][95], but it is more difficult to convincingly demonstrate changes in foetal-derived EVs in disease. Post-translational modifications such as glycosylation increase diversity of these markers.…”
Section: Biomarker Discoverymentioning
confidence: 99%